2011
DOI: 10.1158/1078-0432.ccr-10-2346
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Analysis of KIT Aberrations in Chinese Patients with Melanoma

Abstract: Purpose: KIT aberrations were described in acral and mucosal melanomas in largely Caucasian populations. Asian populations are more prone to develop acral and mucosal than cutaneous melanomas, and may harbor a high frequency of KIT aberrations.Experimental Design: Melanoma subtypes (n ¼ 502) were analyzed histologically to determine melanoma subtype. Tissue samples were analyzed for mutations in exons 9, 11, 13, 17, and 18 of KIT gene in genomic DNA by PCR amplification and Sanger sequencing. The copy numbers … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
123
8
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 217 publications
(151 citation statements)
references
References 33 publications
(85 reference statements)
15
123
8
5
Order By: Relevance
“…In our previous study, increased KIT copy number and KIT mutations were identified in approximately 30% and 7.6% of Chinese melanoma patients, respectively [8]. KIT mutations were detected in 20.7% of CSD, 11.9% of acral, and 9.6% of mucosal melanomas in a Chinese patient cohort (n 5 502) [9].…”
Section: Introductionmentioning
confidence: 82%
“…In our previous study, increased KIT copy number and KIT mutations were identified in approximately 30% and 7.6% of Chinese melanoma patients, respectively [8]. KIT mutations were detected in 20.7% of CSD, 11.9% of acral, and 9.6% of mucosal melanomas in a Chinese patient cohort (n 5 502) [9].…”
Section: Introductionmentioning
confidence: 82%
“…Although the precise reasons for lack of correlation between genetic sequencing and c-KIT immunohistochemical expression are not clear, ours is not the first study to note lack of correlation. 36,37 We recently observed a poor correlation between CD117 staining and c-KIT sequencing in atypical acral nevi. 38 Briefly, we noted that CD117 stained 80% of acral nevi (with and without atypia), but genomic analyses of KIT exon regions 11, 13 and 17 revealed no abnormalities in 'hotspots' frequently associated with point mutations in acral melanomas.…”
Section: Discussionmentioning
confidence: 98%
“…These alterations are disproportionately found in acral and mucosal melanomas, being present in ~10% of these less-common forms of melanoma 18 . Among the well-described tumour-suppressor genes, CDKN2A mutation is detected in ~50% of advanced-stage melanomas, and can rarely overlap with PTEN deletion (FIG.…”
Section: Genetic and Immune Landscape Of Melanomamentioning
confidence: 99%